Relationship lending and competiiton: higher switching cost does not necessarily imply greater relationship benefits - Timo Vesala (Bank of Finland, 2005)
This paper studies relationship lending in a framework where the cost of switching banks measures the degree of banking competition. The relationship lender's (insider bank's) informational advantage creates a lock-in effect, which is at its height when the switching cost is infinitesimal.This is because a low switching cost gives rise to a potential adverse selection problem, and outsider banks are thus reluctant to make overly aggressive bids.This effect gradually fades as the magnitude of the switching cost increases, which de facto reduces the insider bank's profits.However, after a certain threshold in the switching cost, the insider bank's 'mark-up' begins to increase again.Hence, relationship benefits are a non-monotonous (V-shaped) function of the switching cost.The 'dynamic implication' of this pattern is that relationship formation should be more common under extreme market structures ie when the cost of switching banks is either very low or sufficiently high.Recent empirical evidence lends support to this prediction.
URN:NBN:fi:bof-20140807562
Keywords: G21; G24; D82; D43; 330; relationship lending; switching cost; banking competition